Rural Access and Mobility in Pakistan : A Policy Note - Essakali, Mohammed Dalil (World Bank, Washington, DC, 2012)
This note presents a number of policy options to improve basic access and promote the mobility of Pakistan's rural population in support of the Government's Poverty Reduction Strategy. This is achieved through more focused and community driven interventions to meet the direct needs of the rural population. The current state of rural accessibility and mobility are examined together with their effect on both the social and economic dimensions of rural poverty. Key challenges and constraints to reform are identified. The note contributes to the current debate within Pakistan with regard to the better targeting of interventions to assist the rural poor. It should also be of interest to policy makers in other countries concerned with how rural transport policy may be developed to meet the Millennium Development Goals.